Leadership in Action: Learning by Design: Developing an Engine for Transforming Your Company - Beer, Michael; Finnström, Magnus (Center for Creative Leadership, 2009)
Traditional leadership development programs often fail to achieve the desired results because they don't focus on learning linked to the company's business strategy and the real day-to-day challenges facing managers. The experience of Sweden-based industrial group Cardo, which built its executive management program from scratch, shows how organizations can unleash the leadership capabilities required to drive transformation and strengthen business results.